Multi-omics in mesial temporal lobe epilepsy with hippocampal sclerosis: Clues into the underlying mechanisms leading to disease. (August 2021) - Bruxel, Estela M.; Bruno, Danielle C.F.; do Canto, Amanda M.; Geraldis, Jaqueline C.; Godoi, Alexandre B; Martin, Mariana; Lopes-Cendes, Iscia
Highlights: The integration across different molecular layers is crucial to understanding complex disorders, such as epilepsies. Moving from an association signal in GWAS to the identification of causative genetic variants has proven to be challenging in the complex epilepsies. The transcriptomic studies have demonstrated that there is a great variety in mechanisms and signalling pathways involved in disease mechanisms in MTLE+HS. Although abundant there are significant limitations in the current – studies about -omics aspects of MTLE+HS. Abstract: Mesial temporal lobe epilepsy (MTLE) is one of the most common types of focal epilepsy in the adult population. MTLE is frequently associated with a specific histopathological lesion in the medial temporal structures, namely hippocampal sclerosis (HS). A significant proportion of patients with MTLE+HS have severe epilepsy, which is often resistant to clinical treatment. For these patients, surgical resection of the epileptogenic lesion can be performed. Our understanding of the underlying mechanisms leading to MTLE+HS has improved significantly over the past few decades. In this review, we aim to present and discuss the most recent findings regarding the genetic determinants of MTLE+HS. Furthermore, we will address studies about transcriptomics, proteomics, metabolomics, and epigenomic signatures of the tissue that is surgically removed from patients with refractory MTLE+HS and animal models of the disorder. We expect to provide an overview and a critical discussion of the findings, limitations, new approaches, and future directions for multi-omics studies in MTLE+HS.